Role of peer educators in behaviour change communication interventions for HIV prevention among people who inject drugs: Systematic review article - Mabuie, Maltez (Technium Social Sciences Journal, 2020)
Currently, there are 13 million People Who Inject Drugs (PWID) in the world of which 1.7 million people are HIV positive. Recent reports demonstrate that the risk of HIV transmission is significantly high among PWID, because these individuals are involved in risky behaviours; for instance, sharing equipment and involving themselves in risky, sexual activities more than the rest of the population. Peer education is a key behaviour change strategy that draws on several theories such as information motivation behaviour skill theory; theory of reasoned action; and diffusion of innovation theory. In particular, peer educators have been considered important agents of behaviour change because they are capable of communicating with PWID and influencing the group norms. The aim of the study is to look at the role of peer educators in behaviour change communication (BCC) intervention to prevent the spread of HIV among PWID. A systematic literature review was used as the method of choice for data collection. In particular, data were drawn from six highly relevant and most recent research journals. The results of this study demonstrate that peer education positively influences the norms, attitudes and believes of PWID. In conclusion, the study provides evidence that peer educators play a fundamental role reducing harm and the spread of HIV. The study proposes the engagement of volunteers who assist PWID with their injections in BCC interventions in order to prevent the transmission of HIV.